1978
DOI: 10.1002/bjs.1800650610
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal tuberculosis in the 1970s: A continuing problem

Abstract: Eight cases of abdominal tuberculosis (5 indigenous and 3 immigrants) treated in Cardiff in the 5-year period 1972-6 were studied to determine clinical presentation, errors in diagnosis and usefulness of investigations. The heterogeneous presentation is reflected in the 7 types of lesion seen in the 8 cases. Anorexia and weight loss were present in all cases and abdominal colic and post-prandial discomfort were common. No patient had diarrhoea, constipation or intestinal obstruction. The clinical diagnosis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

1978
1978
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 8 publications
0
15
0
2
Order By: Relevance
“…The male:female ratio was 23:7. Of the 30 patients, only 4 were born in the UK; the origins of the remainder were India (8), Middle East (7), West Indies (3), Africa (2) and one each from Pakistan, China, Iran, Spain, Sierra Leone and Sri Lanka. Five patients arrived in the UK with the disease, and of the remaining 21 immigrants, 12 had lived in Britain for periods varying between 18 months and 17 years. It was not possible to determine the period of domicile in Britain for the other 9 immigrants.…”
Section: Methodsmentioning
confidence: 99%
“…The male:female ratio was 23:7. Of the 30 patients, only 4 were born in the UK; the origins of the remainder were India (8), Middle East (7), West Indies (3), Africa (2) and one each from Pakistan, China, Iran, Spain, Sierra Leone and Sri Lanka. Five patients arrived in the UK with the disease, and of the remaining 21 immigrants, 12 had lived in Britain for periods varying between 18 months and 17 years. It was not possible to determine the period of domicile in Britain for the other 9 immigrants.…”
Section: Methodsmentioning
confidence: 99%
“…There have been few previous reported series describing abdominal tuberculosis in Britain. [1][2][3][4][5][6][7] Each has contained relatively small numbers of patients and clinical details have been sparsely recorded. These studies have shown that abdominal tuberculosis has few specific features.…”
mentioning
confidence: 99%
“…Focal peripancreatic involvement is even a more rare situation which may mimic a carcinoma of the pancreas or acute or chronic pancreatitis or present with biliary obstruction [1,4,5]. Abdominal pain, anorexia, and weight loss are the symptoms of a carcinoma of body and tail of the pancreas, but these are also the symptoms of abdominal tuberculosis [3,6]. Even at laparotomy, the peripancreatic mass with lymphadenopathy resembled a carcinoma of the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal tuberculosis is now a relatively rare disease, but it remains a clinical diagnostic problem [2,3]. Focal peripancreatic involvement is even a more rare situation which may mimic a carcinoma of the pancreas or acute or chronic pancreatitis or present with biliary obstruction [1,4,5].…”
Section: Discussionmentioning
confidence: 99%